Method for preparing Cu / CuO nanosheet bundle through hydrothermal reduction
A hydrothermal reduction method using controlled heating and ultrasound forms Cu/CuO nanosheet bundles with uniform size and morphology, addressing synthesis challenges and reducing costs, suitable for applications in catalysis and energy storage.
Patent Information
- Application Number
- CN202411299751.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Existing methods for synthesizing Cu/CuO nanomaterials face challenges in achieving uniform morphology and size, high cost, and low yield, with hydrothermal reduction methods requiring high temperatures and long reaction times, and sonochemical methods being difficult to control and costly.
A method involving hydrothermal reduction with controlled step-wise heating, use of weak reducing agents like sodium citrate and macromolecular chain organic stabilizers, and ultrasound to form Cu/CuO nanosheet bundles with uniform size and controllable morphology, utilizing acoustic cavitation and streaming effects to enhance reaction rate and selectivity.
The method enables rapid preparation of Cu/CuO nanosheet bundles with uniform size and controllable morphology at low temperatures, reducing production costs and environmental impact, suitable for applications in catalysis, energy storage, and electronic packaging.
Smart Images

Figure CN119237747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Background Art
[0002] Nano Cu / CuO can show unique physical and chemical properties in the fields of electricity (conductivity, superconductivity), optics (sensitive components such as sensors, photocatalytic degradation), chemical industry (ceramics, glass, antibacterial agents), mechanics (superplasticity, high hardness and strength) and military (propellants and fuel accelerators, infrared absorption function) by virtue of the unique surface effect, quantum size effect, volume effect and quantum tunneling effect of nano-sized materials, and has a wide range of applications. In recent years, researchers have actively explored the synthesis of nano Cu / CuO with different morphologies, including nanoparticles, nanowires, nanosheets, porous, hollow microspheres and other structures. Among them, irregularly shaped (for example, flower-shaped) nano Cu / CuO has attracted much attention due to its larger specific surface area, higher reaction activity, lower reaction temperature and more stable physical and chemical properties.
[0003] At present, the synthesis methods of nano Cu / CuO mainly include template method, coprecipitation method, hydrothermal reduction method, sonochemical method, etc. Among them, the template used in the template method needs to be removed by corrosion and other steps after the synthesis reaction is completed, which damages the synthesized nano Cu / CuO to a certain extent, and the yield of the template method is low. Under the protection of no inducing agent, the Cu / CuO synthesized by the precipitation method has poor morphology and size uniformity. The hydrothermal reduction method has the advantages of controllable morphology and convenient operation. It is suitable for forming various morphologies and special structures. The reaction conditions are low and the operation is simple, but the reaction temperature required for this method is high and the reaction time is long (often a high-temperature reactor is required). At present, the morphology and size uniformity of nano Cu / CuO synthesized by the hydrothermal method still cannot fully meet the needs, and there are limitations in application. The sonochemical hydrothermal reduction method can significantly increase the reaction rate by using the local high temperature and high pressure environment generated by the acoustic cavitation effect, but the reaction is not easy to control, and the microwave reactor is expensive and has high cost, which is limited to small-scale use. Therefore, there is an urgent need for a new synthesis method for rapidly preparing nano Cu / CuO with controllable morphology and size. Summary of the invention
[0004] In view of the above technical problems, the present invention discloses a method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction, which solves the problems of poor uniformity of morphology and size, high cost and low yield in the prior art of synthesizing nano Cu / CuO.
[0005] To this end, the technical solution adopted by the present invention is:
[0006] A method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction comprises the following steps:
[0007] Step S1, dissolving copper salt in water to prepare a precursor solution A;
[0008] Step S2, dissolving a reducing agent in water to prepare a solution B; the reducing agent is one or a mixture of two or more of sodium citrate, polyethylene glycol, and glucose;
[0009] Step S3, stirring solution B, step-wise heating to 60-120°C, dripping precursor solution A, reacting for 20-40 minutes, and obtaining solution C; wherein, the molar ratio of the reducing agent to the copper salt is 1:2-6, and the temperature of the dripped precursor solution A is lower than 15°C; the step-wise heating refers to first rapidly heating to 50°C at a heating rate of not less than 12°C / min, and then slowly heating to the reaction temperature of 60-120°C at a heating rate of not more than 8°C / min; here, maintaining rapid heating and slow heating to reach the reaction temperature to promote "explosive" nucleation.
[0010] Step S4, adding alkali to solution C to adjust the pH value of the solution to 13-14, then adding a macromolecular chain organic stabilizer aqueous solution to obtain a dark blue mixed solution, superimposing an ultrasonic reaction on the mixed solution at 60-120° C. for 5-30 minutes; when the mixed solution changes from dark blue to green and then to black-red, placing it in a cooling medium or cooling environment and rapidly cooling it to room temperature to obtain a suspension; wherein the macromolecular chain organic stabilizer is one or a mixture of two or more of polyvinyl pyrrolidone, bovine serum albumin, and polydimethyldiallylammonium chloride;
[0011] Step S5, separating, washing and drying the suspension to obtain Cu / CuO nanosheet bundle powder.
[0012] Among them, the reducing agent uses weak reducing agents such as sodium citrate, polyethylene glycol, and glucose. These reducing agents have hydroxyl groups on their tail structures. Under a reaction environment with a specific pH value and sufficient reaction time, nano Cu / CuO can be uniformly grown along a specific direction to form a nanosheet bundle structure with uniform size. Moreover, the use of these weak reducing agents can adjust the relative content and ratio of CuO and Cu (not just a single nano Cu) by optimizing the reaction conditions. Secondly, it can control the limited reduction of Cu ions and control the reaction rate.
[0013] The molar ratio of the reducing agent to the copper salt is selected to be 1:2 to 6. When the molar ratio of the reducing agent to the copper salt is greater than 1:2, a large amount of Cu ions remain in the reaction solution, resulting in a waste of raw materials. At the same time, after the subsequent addition of sodium hydroxide solution, a large amount of copper hydroxide precipitates may be produced, mixed in the nano Cu / CuO powder, reducing the purity of the product; and when the molar ratio is less than 1:6, the purity of the nano Cu / CuO powder does not change much with the increase of the reducing agent concentration, and adding too much reducing agent will also cause corresponding waste. Polyvinyl pyrrolidone, bovine serum albumin, polydimethyldiallyl ammonium chloride and other macromolecular chain organic stabilizers are used. The long hydrophobic carbon chains contained in these macromolecular chain organic stabilizers produce a large repulsive force, forming a steric hindrance effect, effectively preventing the aggregation of nanoparticles, and reducing the size of nano Cu or CuO. At the same time, the amine / amino part contained has a certain reducibility, which is conducive to improving the reduction rate. In addition, the selection of the above stabilizers also fully considers the concept of green chemistry, and the stabilizers are all non-toxic chemicals.
[0014] Sodium hydroxide solution is added to adjust the pH value of the solution to 13-14, wherein the hydroxide ions and the copper ions in the copper salt form copper hydroxide precipitation, which inhibits the large-scale ionization of copper ions and promotes the conversion of limited copper ions into copper atoms, thereby facilitating the formation of nano Cu / CuO with uniform size and fine particle size. Combined with ultrasound, supercooling dropwise addition and other conditions, the obtained nano Cu / CuO has uniform size and fine particle size.
[0015] The Cu / CuO nanosheet bundles prepared by this technical solution have uniform size and controllable morphology, and can be rod-shaped, fiber-shaped, flower-shaped or thorn-shaped, and have low cost and high yield.
[0016] As a further improvement of the present invention, the step-wise heating is: rapidly heating to 50°C at a rate of about 15°C / min, and then slowly heating to 60-120°C at a rate of 5-8°C / min.
[0017] As a further improvement of the present invention, the temperature of the added precursor solution A is lower than 10°C.
[0018] As a further improvement of the present invention, when the reducing agent is sodium citrate, the molar ratio of sodium citrate to the copper salt is 1:3.
[0019] As a further improvement of the present invention, the alkali is a solution that can provide hydroxide ions, such as a sodium hydroxide solution and a potassium hydroxide solution.
[0020] As a further improvement of the present invention, in step S3, the superimposed ultrasound loading method is high-frequency pulse lateral loading. This technical solution uses the acoustic streaming effect of ultrasound and the lateral micromechanical vibration effect, and the lateral wave vibration can quickly reach the arc thin walls on both sides of the reaction container, forming an acoustic wave gradient and laminar flow at the nonlinear boundary (arc thin wall), greatly improving the reaction rate and product yield.
[0021] More preferably, the ultrasonic frequency is 40-60kHz and the sound intensity is less than 5W / cm 2 Appropriate ultrasonic frequency and ultrasonic intensity can form a strong shock wave with the help of acoustic cavitation effect, generate a large number of tiny cavitation bubbles, and use these cavitation bubbles as nucleation particles, significantly reduce the reaction activation energy, and promote the formation of tiny Cu or CuO nanosheets; excessive frequency and intensity will destroy the original structure and original morphology of the synthesized nano-Cu / CuO.
[0022] Preferably, each pulse is loaded with ultrasound for 1 to 2 seconds and idle for 2 to 4 seconds. The loading time should not be continuous for more than 20 minutes, as too long continuous loading time may easily lead to damage to the ultrasound head.
[0023] As a further improvement of the present invention, in step S1, the copper salt is a mixture of one or both of copper acetate and copper ethylene acetonate; in the precursor solution A, the molar concentration of the copper salt is 0.05-0.2 mol / L. With this technical solution, the ligand structure formed by Cu-O in copper acetate and copper ethylene acetonate gives it good chemical stability, and can inhibit the ionization rate of Cu ions during the reaction, thereby controlling the nucleation and growth rate of Cu atoms, and further controlling the size and morphology of nano Cu / CuO in combination with the reaction conditions.
[0024] As a further improvement of the present invention, in step S3, the temperature is raised to 60-80°C in a step-by-step manner. In order to increase the specific surface area of nano Cu / CuO to obtain higher reaction catalytic activity, it is often necessary to generate more flower-shaped CuO. In step S3, the optimal reaction temperature can be adjusted according to the relative yield of nano Cu and CuO to be obtained. This technical solution uses a step-by-step slow temperature increase and maintains a low temperature reaction temperature, which can promote the growth of a large number of CuO nanosheet bundles.
[0025] As a further improvement of the present invention, the dropping speed of the precursor solution A is 0.5-0.8 mL / min. By adopting this technical solution, the copper salt below 15°C is added to the reaction solution, which can increase the non-uniform nucleation sites of Cu or CuO clusters, promote the large-area rapid nucleation of Cu or CuO clusters, thereby reducing the particle size of nano Cu or CuO and improving the uniformity.
[0026] As a further improvement of the present invention, the particle size of Cu or CuO can be controlled by using a droplet addition speed of 0.5 to 0.8 mL / min. A high droplet addition speed will cause a large number of Cu or CuO clusters to aggregate in the solution, thereby producing a product with a larger size (1 micron or even tens of microns), which is not conducive to exerting the high surface energy advantage of nanoscale materials.
[0027] As a further improvement of the present invention, a double-layer burette is used, the outer layer is passed through with ice salt water, and the inner layer is used for controllable dripping of copper salt. Furthermore, a rubber sleeve is coated between the two layers.
[0028] As a further improvement of the present invention, the mass concentration of the macromolecular chain organic stabilizer aqueous solution is 2 to 8.5 g / L. Controlling the mass concentration of these stabilizers to 2 to 8.5 g / L and then adding them to solution C can better control the particle size and morphology. When too low a mass concentration is selected, the coating barrier effect of the stabilizer is poor and the particle size is relatively uneven; when the mass concentration of the stabilizer is too high, the stabilizer bridges itself and aggregates together, which only has a limited coating effect and reduces the size uniformity.
[0029] As a further improvement of the present invention, the macromolecular chain organic stabilizer is polyvinyl pyrrolidone. Further preferably, the quality grade of the polyvinyl pyrrolidone is K30, and the relative molecular mass is 30,000 to 40,000.
[0030] As a further improvement of the present invention, the cooling medium is ice water or ice salt water. The reaction process is an exothermic reaction, and an ice water bath or an ice salt water bath can cool the reaction solution to room temperature at a very fast speed, quickly consume the residual heat in the reaction solution, and prevent the nanosheet bundles from agglomerating.
[0031] As a further improvement of the present invention, in step S5, the suspension is ultrasonically dispersed for 5 minutes, then centrifuged, and deionized water and ethanol are added to the black-red precipitate for three times of centrifugal washing and ultrasonic dispersion. Furthermore, the cleaned black-red precipitate is finally immersed in ethanol for standby use.
[0032] As a further improvement of the present invention, in step S5, the centrifugal speed is 2000-4000 r / min, and the centrifugal time is 12-15 min. In this technical solution, the size of the synthesized single Cu or CuO nanosheet bundle powder is about 100 nm, and the main solvent is deionized water. Therefore, a moderate centrifugal speed and a relatively low centrifugal time can separate the nanosheet bundle powder from the reaction solution.
[0033] As a further improvement of the present invention, in step S5, vacuum drying is adopted, and the vacuum drying temperature is not more than 60°C, in order to prevent the obtained part of the Cu nanosheet bundle powder from being oxidized to CuO in the air. Further preferably, the vacuum drying temperature is room temperature, the time is 6 to 24 hours, and it is placed in a -5°C to -20°C environment for storage.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] First, the technical solution of the present invention improves the traditional hydrothermal reduction process. After briefly applying ultrasound + low-temperature hydrothermal reduction, the Cu / CuO nanosheet bundles with uniform size and controllable morphology are quickly (5 minutes) prepared at low temperature (as low as 60°C) by means of acoustic cavitation effect and acoustic streaming effect. Nanosheets of various forms and structures can be formed, with a large specific surface area, which can give full play to the advantages of the nanostructure itself, show high reaction catalytic activity and specific physical and chemical properties, and the synthesis process is simple, the reaction conditions are low, and the cost is low. It is suitable for catalytic decomposition, energy batteries, electronic packaging materials and other fields.
[0036] Second, the reaction of the technical solution of the present invention is carried out under low-temperature ultrasonic conditions throughout the process. Compared with the complex synthesis process of the prior art, it avoids the harsh conditions of high temperature and high pressure, and does not require additional growth inducing agents. It has extremely low requirements for reaction conditions and a high reaction rate. At the same time, this method has strong selectivity and can well control the purity and relative content of Cu / CuO nanosheets, thereby realizing low-cost, low-energy consumption mass production of nano Cu / CuO products. In addition, the short-term ultrasonic and low-temperature environment effectively reduces the corrosion and loss of the ultrasonic head in the reaction solution, reduces the replacement frequency of the ultrasonic head, and further reduces costs.
[0037] Third, the technical solution of the present invention uses water as a solvent, which, on the one hand, reduces the use of toxic organic solvents such as ethylene glycol and chloroform, and on the other hand, improves the conversion rate and selectivity of the reduction reaction. At the same time, the solutes and stabilizers used are non-toxic or extremely low in toxicity, which prevents pollution while achieving effective utilization of resources, and is in line with the principles of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The scanning electron microscope / secondary electron mode (SEM / SE) image of the fibrous and flower-shaped mixed Cu / CuO nanosheet bundle obtained in Example 1 of the present invention and its local morphology magnified image; (a) low-magnification SEM / SE image, (b) local morphology magnified image;
[0039] Figure 2The SEM / SE images of the peony-shaped Cu / CuO nanosheet bundle obtained in Example 2 of the present invention and the magnified image of its local morphology; (a) low-magnification SEM / SE image, (b) magnified image of the local morphology;
[0040] Figure 3 The SEM / SE images of the chrysanthemum-shaped Cu / CuO nanosheet bundle obtained in Example 3 of the present invention and the enlarged image of its local morphology; (a) low-magnification SEM / SE image, (b) enlarged image of the local morphology;
[0041] Figure 4 The SEM / SE images of the rod-shaped and thorn-shaped Cu / CuO nanosheet bundles obtained in Example 4 of the present invention and the magnified images of their local morphology; (a) low-magnification SEM / SE image, (b) magnified image of the local morphology;
[0042] Figure 5 This is an energy dispersive spectrometer (EDS) surface scanning element distribution diagram of the peony-shaped Cu / CuO nanosheet bundle obtained in Example 2 of the present invention;
[0043] Figure 6 This is the X-ray diffraction (XRD) spectrum of the peony-shaped Cu / CuO nanosheet bundle obtained in Example 2 of the present invention.
[0044] Figure 7 The following are comparison photos of the solutions after ultrasonic reaction of Example 1 of the present invention and Comparative Examples 1 and 2; wherein a and b are Comparative Example 1, c and d are Example 1, and e and f are Comparative Example 2.
[0045] Figure 8 This is a picture after adding sodium hydroxide in step S6 of comparative example 3 of the present invention. DETAILED DESCRIPTION
[0046] The preferred embodiments of the present invention are described in further detail below.
[0047] Example 1
[0048] This embodiment provides a method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction, comprising the following steps:
[0049] S1. Dissolve 1.04 g of copper acetate monohydrate in 100 mL of deionized water and stir magnetically at room temperature for 20 min to prepare precursor solution A;
[0050] S2. Dissolve 2.95 g of sodium citrate in 100 mL of deionized water to prepare solution B;
[0051] S3. Under magnetic stirring, the temperature of solution B in an oil bath is raised to 60-80°C in a stepwise manner and allowed to stand for 5 minutes. A 15°C precursor solution A is added dropwise to solution B using a conventional burette at a rate of 0.8 mL / min. After the addition is complete, the solution is reacted for 30 minutes and a light blue solution C is obtained after stirring. The stepwise heating refers to rapidly raising the temperature to 50°C at a rate of about 15°C / min, and then slowly raising the temperature to 60-80°C at a rate of 5-8°C / min. The stepwise heating and low-temperature reaction conditions are more conducive to maintaining the size uniformity and stability of the reaction product.
[0052] S4. Dissolve 4.02 g of sodium hydroxide in 100 mL of deionized water to prepare solution D;
[0053] S5. 0.21 g of polyvinyl pyrrolidone was dissolved in 100 mL of deionized water to prepare solution E, which hindered the aggregation of nano-Cu / CuO by steric hindrance effect;
[0054] S6. Add solution D to solution C, adjust the pH value of the solution to 13, and quickly add solution E to obtain a dark blue solution F; the strong alkaline environment can provide abundant hydroxide ions, which can form insoluble copper hydroxide with Cu ions in the solution, and slowly ionize under the subsequent ultrasound, and produce small-sized nano-Cu / CuO through a reduction reaction;
[0055] S7. Keep solution F at 60-80°C and apply high-frequency pulse transverse ultrasonic reaction for 5 min. The ultrasonic frequency is 40 kHz and the ultrasonic intensity is 0.6-0.84 W / cm 2 Under each pulse, ultrasound was applied for 1s and then left blank for 2s. Solution F quickly changed from dark blue to dark red. After cooling to room temperature in an ice-water bath, dark red suspension G was obtained.
[0056] S8. The suspension G was ultrasonically dispersed for 10 min, and after centrifugation at 3000 r / min for 15 min, the supernatant was poured out, and deionized water and ethanol were added to the lower black-red precipitate for three centrifugal washings and ultrasonic dispersions, and finally the cleaned black-red precipitate was immersed in ethanol for standby use;
[0057] S9. After vacuum drying at room temperature for 6 hours, the Cu / CuO nanosheet bundle powder can be obtained and stored at -5 to -20°C.
[0058] The preparation method of this embodiment is to apply ultrasound for a short time (5min) + low temperature (60°C) hydrothermal reduction method, and use the acoustic cavitation effect, acoustic streaming effect and other effects to quickly prepare fibrous and flower-shaped mixed Cu / CuO nanosheets at low temperature. The average length of a single sheet is 150nm. Figure 1However, due to the combined effects of low reaction temperature, low frequency, intensity and action time of ultrasound application, the size uniformity is poor, and the length of some fibrous sheets exceeds 700nm.
[0059] Nevertheless, compared with the complex synthesis process of the prior art, the sheet bundle synthesized by this method still has a larger specific surface area and surface activity. At the same time, it avoids the harsh conditions of high temperature and high pressure, and the reaction conditions are extremely low, saving production costs. At the same time, water is used as a solvent, which reduces the use of toxic organic solvents such as ethylene glycol and chloroform, and also improves the conversion rate and selectivity of the reduction reaction, meeting the needs of green chemistry. This method can be used for the synthesis of low-cost, high-surface energy Cu / CuO nanosheets.
[0060] Example 2
[0061] This embodiment provides another method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Based on the embodiment 1, the difference between this embodiment and the embodiment 1 is as follows:
[0062] In step S3, the precursor solution A is added dropwise to the supercooled solution B (7-9° C.) using a homemade double-layer burette. The temperature in the burette is measured to be 7-9° C. and the dropping speed is 0.8 mL / min.
[0063] In step S5, the mass concentration of polyvinyl pyrrolidone in solution E is increased to 4.4 g / L. The specific steps are as follows: 0.44 g of polyvinyl pyrrolidone is dissolved in 100 mL of deionized water to prepare solution E.
[0064] In step S7, the ultrasonic frequency of the applied ultrasound is 60kHz and the ultrasonic intensity is 1.4-2W / cm 2 .
[0065] The method of this embodiment also rapidly prepared peony-shaped Cu / CuO nanosheet bundles at low temperature by briefly applying ultrasound, but increased the mass concentration of the stabilizer, the ultrasound frequency and the ultrasound intensity on the basis of the specific embodiment 1, and significantly improved the size uniformity of the Cu / CuO nanosheet bundles through a stronger steric hindrance effect and ultrasonic cavitation effect, and reduced the size of the nanosheets. Figure 2 As shown, the uniformity and dispersion of the peony-shaped Cu / CuO nanosheet bundles are relatively good. The overall size of the flower is about 600nm, and the average length of a single sheet bundle is less than 100nm, showing a high specific surface area. Figure 5 and Figure 6 The corresponding elemental composition content and phase of the nanosheet bundle are shown respectively. At the same time, the synthesis efficiency and product yield of this method are also high, which fully meets the synthesis needs of low cost, large batch and green chemistry.
[0066] Example 3
[0067] This embodiment provides another method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Based on Example 2, this embodiment is different from Example 2 in that:
[0068] In step S5, the mass concentration of polyvinyl pyrrolidone in solution E is increased to 8.1 g / L. The specific steps are as follows: 0.81 g of polyvinyl pyrrolidone is dissolved in 100 mL of deionized water to prepare solution E.
[0069] In step S7, the ultrasonic frequency of the applied ultrasound is 60kHz and the ultrasonic intensity is 3.4-4.4W / cm 2 .
[0070] This embodiment further increases the mass concentration of the stabilizer, the ultrasonic frequency and the ultrasonic intensity on the basis of the specific embodiment 1, and quickly prepares the daisy-shaped Cu / CuO nanosheet bundles at low temperature, and the average size of a single sheet bundle is further reduced, such as Figure 3 However, due to the high-frequency and high-intensity ultrasound, more polyvinyl pyrrolidone was polymerized first and could not achieve a good coating effect, and the size uniformity and stability of the nanosheet bundles decreased. Considering the effects of reaction concentration and ultrasound process parameters, this method can be used to synthesize low-cost, high-surface energy Cu / CuO nanosheet bundles.
[0071] Example 4
[0072] This example provides another method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Based on Example 1, this example is different from Example 1, Example 2 and Example 3 in that:
[0073] In step S3, the precursor solution A is supercooled and added dropwise to the solution B using a homemade double-layer burette. The temperature in the burette is measured to be 5-8° C. and the adding speed is 0.5 mL / min.
[0074] In step S7, solution F is maintained at 60-80°C and subjected to high-frequency pulse transverse ultrasonic reaction for 10 minutes, with an ultrasonic frequency of 60 kHz and an ultrasonic intensity of less than 0.2 W / cm 2 .
[0075] The method of this embodiment rapidly prepares uniformly sized rod-shaped and thorn-shaped mixed Cu / CuO nanosheets at low temperature, such as Figure 4As shown, from the morphology, there are a large number of small thorns similar to secondary dendrites on the surface of the nanosheet. The supercooling dripping of the appropriate temperature in this embodiment can increase the non-uniform nucleation site, thereby promoting large-area rapid nucleation, ensuring the small size and high uniformity of the synthesized nano Cu or CuO. At the same time, a higher degree of supercooling will cause the nano Cu or CuO clusters to grow along a specific direction during the conversion of nanosheets, thereby forming a rod-shaped and thorn-shaped mixed Cu or CuO nanosheet. The high-frequency, low-intensity and long-term ultrasonic action makes this morphology stably inherited (the thorn-like structure is not destroyed). These thorn-like structures are used in fields such as chemical catalysis in addition to having a higher specific surface area, and are also expected to achieve good physical properties such as high strength and high electrochemical properties by mechanical interlocking or embedding, thereby widening its scope of application.
[0076] Example 5
[0077] This embodiment provides another method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Based on the embodiment 1, this embodiment differs from the embodiment 1 mainly in the following steps:
[0078] S1. 3.14 g of copper ethylene acetonate was dissolved in 100 mL of deionized water and stirred under magnetic force at 60°C for 30 min to prepare a precursor solution A. Since copper ethylene acetonate is insoluble in water, A is actually a suspension. In the subsequent reaction, the insoluble copper ethylene acetonate can release Cu ions to a limited extent, thereby forming a nanosheet bundle of smaller size.
[0079] S2. 6.19 g of sodium citrate and 3.6 g of glucose were dissolved in 100 mL of deionized water to prepare solution B; the mixture of the two reducing agents can reduce the required reaction time;
[0080] S3. Heat solution B in an oil bath stepwise to 120°C under magnetic stirring and let stand for 5 min. Use a supercooled burette to drop precursor solution A into solution B at a rate of 0.5 mL / min. After the addition is complete, react for 40 min and obtain a light blue solution C after stirring.
[0081] S4. The pH of solution C was adjusted to 13, and 0.32 g of polyvinyl pyrrolidone and 0.12 g of polydimethyldiallyl ammonium chloride were dissolved in 100 mL of deionized water to prepare solution E. A co-stabilizer was used to reduce the size of nano-Cu / CuO and promote the rapid sedimentation of nano-Cu / CuO through the steric hindrance effect of the long carbon chain in polyvinyl pyrrolidone and the electrostatic attraction of the quaternary ammonium salt group in polydimethyldiallyl ammonium chloride.
[0082] S5. Rapidly add solution E to solution C to obtain a dark blue solution F;
[0083] S6. Solution F was maintained at 120°C and subjected to high-frequency pulse transverse ultrasonic reaction for 30 min, with an ultrasonic frequency of 60 kHz and an ultrasonic intensity of 2 to 2.4 W / cm 2 Under each pulse, ultrasound was applied for 1s and then left blank for 2s. Solution F quickly changed from dark blue to dark red. After cooling to room temperature in an ice-water bath, dark red suspension G was obtained.
[0084] S8. After the suspension G is ultrasonically dispersed and centrifuged, the supernatant is poured out, and deionized water and ethanol are added to the lower layer of black-red precipitate for three centrifugal washings and ultrasonic dispersions, and finally the cleaned black-red precipitate is immersed in ethanol for standby use;
[0085] S9. After vacuum drying, the Cu nanosheet powder can be obtained and stored at -5 to -20°C.
[0086] The preparation method of this embodiment uses ultrasound and hydrothermal reduction to quickly prepare Cu nanosheets by means of acoustic cavitation effect, acoustic streaming effect and common coating agent. The length of the nanosheet is about 200nm, the thickness is less than 40nm, and the size uniformity and dispersion are good. At the same time, its good mechanical properties and electrical properties have great application value in the fields of energy, battery and electronic packaging.
[0087] Example 6
[0088] This embodiment provides another method for preparing Cu / CuO nanosheet bundles by hydrothermal reduction. Based on Example 5, this embodiment is different from Example 5 in that:
[0089] In step S2, 11.2 g of polyethylene glycol is dissolved in 100 mL of deionized water to prepare solution B; polyethylene glycol; polyethylene glycol itself has reducing properties and structure-directing properties and can synthesize fine one-dimensional nanomaterials.
[0090] Before step S4, a sodium hydroxide solution still needs to be prepared, and the specific steps are as follows: 4.02 g of sodium hydroxide is dissolved in 100 mL of deionized water to prepare solution D. In step S4, 0.42 g of polyvinyl pyrrolidone is dissolved in 100 mL of deionized water to prepare solution E.
[0091] The method of this embodiment finally obtains fibrous Cu nanosheet bundle powder, or Cu nanofiber, which has good straightness and uniformity, a linear dimension of less than 50 nm, and has application value in the field of flexible electronic manufacturing and electronic packaging.
[0092] The above methods all use a method of briefly applying ultrasound + low-temperature hydrothermal reduction to quickly prepare Cu / CuO nanosheet bundles with uniform size and controllable morphology at low temperature, and form nanosheets of various forms and structures, which have a large specific surface area and can give full play to the inherent advantages of the nanostructure, showing high reaction catalytic activity and specific physical and chemical properties. At the same time, the harsh conditions of high temperature and high pressure are avoided, the reaction conditions are extremely low, and production costs are saved. In addition, using water as a solvent reduces the use of toxic organic solvents such as ethylene glycol and chloroform, and also improves the conversion rate and selectivity of the reduction reaction, meeting the needs of green chemistry. This method can be used for the synthesis of low-cost, high-surface energy Cu / CuO nanosheet bundles.
[0093] Comparative Example 1
[0094] On the basis of Examples 1 to 6, the frequency and intensity of ultrasound in this comparative example are different, mainly as follows:
[0095] The ultrasonic frequency of the high-frequency pulsed ultrasound was 20 kHz and the ultrasonic intensity was 0.2 W / cm 2 (Ultra-low frequency and low intensity). Due to the ultra-low ultrasonic frequency and low intensity, the ultrasonic cavitation and acoustic streaming effects are weak. After 20 minutes of reaction, only a small amount of black nano-CuO can be produced, and even no black nano-CuO can be seen at the bottom. It is unable to continue to reduce to generate nano-Cu. The final suspension is as follows: Figure 7 As shown in a and b, the solution is still blue, which means that the Cu ions are not completely reduced under the non-ultrasonic or ultra-low ultrasonic process. Figure 7 As shown in c and d (the situations in Examples 1 to 6 are the same, only the two tubes in Example 1 are listed for comparison), the solutions in Examples 1 to 6 to which appropriate ultrasonic process parameters are applied are transparent, and the bottom of the centrifuge tube is the generated nano Cu / CuO powder.
[0096] Comparative Example 2
[0097] Based on Comparative Example 1, the difference of this comparative example is that the ultrasonic frequency of the high-frequency pulse ultrasound is 70kHz and the ultrasonic intensity is 5W / cm 2 (Ultra-high frequency and high intensity). Since conventional ultrasonic generators cannot achieve frequencies exceeding 60kHz, here we place the reaction container in a large steel tank filled with water, and directly insert a large transducer into the water in the steel tank to apply ultra-high frequency ultrasound, and then put the reaction solution into a centrifuge tube. Figure 7 As shown in e and f on the right side of the figure, the obtained reaction product is the same as that in Example ( Figure 7 There is little difference between c) and d). The excessively high frequency and intensity here cannot further refine the powder size and improve the surface properties, but further increase the production cost (large transducers, ultrasonic generators and other components, and consider their maintenance) and reduce production efficiency.
[0098] In summary, Comparative Examples 1 and 2 cannot achieve the desired results of low cost, high efficiency, and uniform and small size.
[0099] Comparative Example 3
[0100] Based on Example 2, the difference of this comparative example is that the dropping speed is 5 mL / min, a large number of copper ions are nucleated and immediately adsorbed and grown after the reaction in step S3, and then, after sodium hydroxide is added in step S6, a flocculent substance appears, such as Figure 8 As shown. Finally, the desired product is not obtained. Finally, the particle size becomes larger and contains impurities such as copper hydroxide.
[0101] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing Cu / CuO nanosheets by hydrothermal reduction, characterized in that: The steps include: Step S1, dissolving copper salt in water to prepare a precursor solution A; Step S2, dissolving a reducing agent in water to prepare a solution B; the reducing agent is one or a mixture of two or more of sodium citrate, polyethylene glycol, and glucose; Step S3, stirring solution B, stepwise heating to 60-120°C, adding precursor solution A dropwise, reacting for 20-40min, and obtaining solution C; wherein the molar ratio of the reducing agent to the copper salt is 1:2-6, and the temperature of the precursor solution A is lower than 15°C; the stepwise heating refers to first rapidly heating to 50°C at a heating rate of not less than 12°C / min, and then slowly heating to a reaction temperature of 60-120°C at a heating rate of not more than 8°C / min; Step S4, adding alkali to solution C to adjust the pH value of the solution to 13-14, then adding a macromolecular chain organic stabilizer aqueous solution to obtain a dark blue mixed solution, superimposing an ultrasonic reaction on the mixed solution at 60-120° C. for 5 min-30 min; when the mixed solution turns into black-red, placing it in a cooling medium or a cooling environment to quickly cool it to room temperature to obtain a suspension; wherein the macromolecular chain organic stabilizer is one or a mixture of two or more of polyvinyl pyrrolidone, bovine serum albumin, and polydimethyldiallylammonium chloride; Step S5, separating, washing and drying the suspension to obtain Cu / CuO nanosheet bundle powder.
2. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 1, characterized in that: In step S3, the superimposed ultrasound loading method is high-frequency pulse lateral loading, the ultrasound frequency is 40-60kHz, and the sound intensity is less than 5W / cm 2 Under each pulse, ultrasound is loaded for 1 to 2 seconds and then idle for 2 to 4 seconds.
3. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 2, characterized in that: In step S1, the copper salt is one of copper acetate and copper ethylene acetonide or a mixture of both; in the precursor solution A, the molar concentration of the copper salt is 0.05-0.2 mol / L.
4. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 2, characterized in that: In step S3, the temperature is raised to 60-80° C. in a stepwise manner; the precursor solution A is added dropwise at a rate of 0.5-0.8 mL / min.
5. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 2, characterized in that: The mass concentration of the macromolecular chain organic stabilizer aqueous solution is 2-8.5 g / L.
6. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 2, characterized in that: The cooling medium is ice water or ice brine.
7. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to any one of claims 1 to 6, characterized in that: In step S5, the suspension is ultrasonically dispersed for 5 minutes and then centrifuged. Deionized water and ethanol are added to the black-red precipitate to perform centrifugal washing and ultrasonic dispersion three times.
8. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 7, characterized in that: In step S5, the centrifugal speed is 2000-4000 r / min, and the centrifugal time is 12-15 min.
9. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 7, characterized in that: In step S5, vacuum drying is adopted, and the temperature of vacuum drying is not more than 60°C.
10. The method for preparing Cu / CuO nanosheets by hydrothermal reduction according to claim 7, characterized in that: The vacuum drying temperature is room temperature and the time is 6 to 24 hours.
Citation Information
Patent Citations
Processing method of primary-color efficient smallanthus sonchifolius dry powder
CN109965237A
Green and environment-friendly conductive nano-copper ink and preparation method thereof
CN111496266A
Method for ultrasonically preparing nano-copper particles at room temperature and preparation method of copper powder
CN117816968A
Pyrotechnical compositions manufacturing method
RU2663047C1
Targeted microbubble, preparation method thereof, and use thereof
US20210008230A1